Separation of mixtures by a combination of crystallization and continuous distillation processes using heat pumps - G. A. Nosov; V. I. Bel’skaya; V. S. Zhil’tsov (Тонкие химические технологии)
Some variants of separation of binary eutectic mixtures by combining the processes of fractional crystallization and continuous distillation with using heat pumps are considered. Influence of technological parameters on the yield and energy efficiency of the process in relation to the separation of a binary mixture of benzene and naphthalene is analyzed. It is shown that use of compression heat pumps can significantly reduce energy costs for the separation process.